2015
DOI: 10.1017/s1041610215001830
|View full text |Cite
|
Sign up to set email alerts
|

Group and individual cognitive therapies in Alzheimer's disease: the ETNA3 randomized trial

Abstract: These findings challenge current management practices of Alzheimer's patients. While cognitive-oriented group therapies have gained popularity, this trial does not show improvement for the patients. The individualized cognitive rehabilitation intervention provided clinically significant results. Individual interventions should be considered to delay institutionalization in Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(141 citation statements)
references
References 32 publications
7
120
2
9
Order By: Relevance
“…22 Previous reviews reported that cognitive stimulation therapy and cognitive training are not effective at reducing cognitive decline, while there was some evidence for individual cognitive rehabilitation from a single trial. 35 Our findings are in line with current theoretical models describing how best to support people with dementia to live at home. 35 Our findings are in line with current theoretical models describing how best to support people with dementia to live at home.…”
Section: Discussionsupporting
confidence: 89%
“…22 Previous reviews reported that cognitive stimulation therapy and cognitive training are not effective at reducing cognitive decline, while there was some evidence for individual cognitive rehabilitation from a single trial. 35 Our findings are in line with current theoretical models describing how best to support people with dementia to live at home. 35 Our findings are in line with current theoretical models describing how best to support people with dementia to live at home.…”
Section: Discussionsupporting
confidence: 89%
“…In these two studies, patients of the experimental group increased their cognition relatively more than the control group after intervention, both for the ADAS-Cog and the MMSE. Other studies showed no significant differences between the conditions with regard to cognition [34,35,45,46,49,51,55,57,58]. Studies that used other assessment tools to measure cognitive impairment showed also positive effects.…”
Section: Skills Training Trialsmentioning
confidence: 94%
“…Most studies included elderly with mild cognitive impairments [35, 36, 41-43, 47, 49-51, 53, 55, 56], some studies included elderly at risk for dementia [38,52,58], some other studies patients with mild to moderate dementia [37,46,57], moderate to severe dementia [34,48], diagnosed with Alzheimer disease [39,40,44,45,48,51,54].…”
Section: Skills Training Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive rehabilitation is usually carried out in the setting where the person lives or undertakes activities, to ensure direct relevance, and carers and families, when available and willing, are fully involved and appropriately supported. There is a small but growing evidence base demonstrating that cognitive rehabilitation is effective in supporting everyday functioning, reducing disability, and delaying institutionalization [1115]. …”
Section: How Can Cognitive Rehabilitation Benefit People With Dementimentioning
confidence: 99%